CARDIORESPIRATORY FITNESS ASSOCIATED TO TEENAGERS’ FAT: VO2MAX CUTOFF POINT - Smouter,Leandro (2019)
ABSTRACT Objective: To associate the Maximal Oxygen Uptake (VO2max) with body fat percentage (%BF), and to establish the best VO2max cutoff point for predicting risk %BF in teenagers. Methods: This study was carried out with 979 subjects aged 10 to 18.8 years, 556 (56.8%) girls. The 20 m shuttle run protocol determined the VO2max, which was analyzed in quintiles and in a numeric scale. Cutaneous fold equations determined the %BF, later classified as risk to health/obesity when >25 in girls and >20 in boys. Regression method was used - Odds Ratio (OR) and Receiver Operating Characteristics Curve (ROC curve) with α <5%. Results: From the total number of valid cases, 341 (65.6%) girls and 202 (53.2%) boys presented %BF of risk, and a larger proportion of %BF of risk was observed in the 1st quintile of the VO2max for both genders. There was inverse association between VO2max and %BF of risk from the 4th quintile (OR 1.84, 95%CI 1.05-3.24) until the 1st quintile (OR 4.74, 95%CI 2.44-9.19) for girls, and from the 2nd quintile (OR 2.99, 95%CI 1.48-6.00) until the 1st quintile (OR 5.60, 95%CI 2.64-11.87) for boys. As analytic highlights, VO2max Cutoff points for prediction of %BF of risk were ≤40.9 mL/kg-1/min-1 (AUC: 0.65; p<0.001) for girls and ≤44.8 mL/kg-1/min-1 (AUC: 0.66; p<0.001)for boys.. Conclusions: VO2max was inversely associated to the %BF, and VO2max cutoff points for prediction of %BF of risk are important results to generate action to fight early obesity.